Analisis Hubungan Beban Kerja dan Stres Kerja pada Karyawan Logistik: Peran Work-Life Balance sebagai Mediator di PT. Wahana Lintas Nusantara - Karimah, Nurul; Nitte, Eka Putri Prinanda; Mujanah, Siti; Fianto, Achmad Yanu Alif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the relationship between workload and job stress among logistics employees at PT. Wahana Lintas Nusantara, highlighting the role of work-life balance as a mediator. In the logistics industry, high workloads often lead to job stress, which negatively impacts employee well-being and company productivity. This research involved 120 operational employees as respondents, who completed questionnaires related to workload, job stress, and work-life balance. Path analysis was employed to identify both direct and indirect relationships among the variables. The findings reveal that workload has a significant positive effect on job stress, indicating that the higher the workload experienced by employees, the greater the level of stress they feel. However, work-life balance plays a significant mediating role, where a balanced work and personal life can mitigate the negative impact of workload on job stress. These findings suggest that company efforts to support work-life balance, such as flexible work schedules, adequate leave, and mental health programs, can help employees manage stress and enhance their well-being. This study provides valuable insights for the management of PT. Wahana Lintas Nusantara in designing policies that promote work-life balance for employees. Furthermore, it contributes to the academic literature on the relationship between workload, job stress, and work-life balance in the logistics sector, particularly in Indonesia.